Novel homozygous sequence variants in the GDF5 gene underlie acromesomelic dysplasia type‐grebe in consanguineous families. (March 2017) - Umair, Muhammad; Rafique, Afzal; Ullah, Asmat; Ahmad, Farooq; Ali, Raja Hussain; Nasir, Abdul; Ansar, Muhammad; Ahmad, Wasim
Abstract: Acromesomelic dysplasia Grebe type (AMDG) is characterized by severe knob like non‐functional fingers and short acromesomelic limbs, and is inherited in an autosomal recessive manner. Disease causing sequence variants in the GDF5 (Growth Differentiation Factor 5) gene located on chromosome 20q11.22 are responsible for causing AMDG. In the study, presented here, two consanguineous families with AMDG were clinically and genetically characterized. After establishing linkage in the two families (A and B) to GDF5 gene on chromosome 20q11.22, Sanger DNA sequencing was performed in all available affected and unaffected members. Sequence analysis of the GDF5 gene revealed two novel variants including a duplication (c.157_158dupC, p.Leu53Profs*41) in family A, and a nonsense (p.Trp291*) in family B. Our findings extend the body of evidence that supports the importance of GDF5 in the development of limbs.